Improving Students’ Listening Skills Through a Local Culture-Based Listening Module Using T2s Application - Fitri Arini; Widiarini Widiarini (SAWERIGADING, 2026)
The purpose of this research is to develop a local culture-based intermediate listening learning module using the T2S (Text to Speech) application and to test its effectiveness. The research method used is the Dick Carey RD research method. The research was conducted in the English Language Education study program with a population and sample of second-semester English Language Education students. Data collection techniques were observation, questionnaires, and interviews. The data analysis technique used was descriptive by analysing quantitative data obtained from expert tests and field tests. The developed module consists of four thematically organized chapters: regional overview, historical figures, local folklore, and culinary and tourism, which are designed to support contextual learning and enhance learners’ familiarity with listening content. The module is also complemented by a dual design, including a Teacher’s Guide and a Student’s Activity Book, to ensure effective classroom implementation and promote learner autonomy. Validation results indicate high feasibility, with language validation reaching 95%, content validation 85%, and media validation 75%, with minor revisions applied to audio pacing and layout. Students’ responses to the module were highly positive, with an overall score of 84%, indicating strong engagement and perceived usefulness. Furthermore, the effectiveness test revealed a significant improvement in students’ listening ability, as reflected in the increase of mean scores from 53.07 to 87.20. The findings suggest that the integration of contextual learning, local cultural content, and T2S technology provides an effective, adaptive, and engaging approach to listening instruction. This study contributes to the growing body of research on technology-enhanced language learning and highlights the importance of culturally relevant materials in improving listening comprehension in EFL settings.  AbstrakTujuan dari penelitian ini adalah untuk mengembangkan modul pembelajaran menyimak tingkat menengah berbasis budaya lokal menggunakan aplikasi T2S (Text to Speech) dan untuk menguji keefektifannya. Metode penelitian yang digunakan adalah metode penelitian Dick Carey RD.Penelitian ini dilakukan di program studi Pendidikan Bahasa Inggris dengan populasi dan sampel mahasiswa Pendidikan Bahasa Inggris semester kedua. Teknik pengumpulan data adalah observasi, kuesioner, dan wawancara. Teknik analisis data yang digunakan adalah deskriptif dengan menganalisis data kuantitatif yang diperoleh dari uji ahli dan uji lapangan. Modul yang dikembangkan terdiri atas empat bab tematik, yaitu gambaran wilayah, tokoh sejarah, cerita rakyat lokal, serta kuliner dan pariwisata, yang dirancang untuk mendukung pembelajaran kontekstual dan meningkatkan keterkaitan materi dengan pengalaman siswa. Modul ini juga dilengkapi dengan desain ganda berupa Buku Panduan Guru dan Buku Aktivitas Siswa untuk mendukung implementasi pembelajaran yang efektif serta mendorong kemandirian belajar. Hasil validasi menunjukkan tingkat kelayakan yang tinggi, dengan validasi bahasa mencapai 95%, validasi isi 85%, dan validasi media 75%, dengan beberapa revisi minor pada aspek kecepatan audio dan tata letak. Respon siswa terhadap modul menunjukkan hasil yang sangat positif dengan skor sebesar 84%, yang mencerminkan tingkat keterlibatan dan kebermanfaatan yang tinggi. Selain itu, hasil uji efektivitas menunjukkan adanya peningkatan yang signifikan pada kemampuan listening siswa, yang ditunjukkan oleh kenaikan nilai rata-rata dari 53,07 menjadi 87,20. Temuan ini menunjukkan bahwa integrasi pendekatan kontekstual, muatan budaya lokal, dan teknologi T2S mampu menciptakan pembelajaran listening yang lebih efektif, adaptif, dan menarik. Penelitian ini memberikan kontribusi terhadap pengembangan pembelajaran bahasa berbasis teknologi serta menegaskan pentingnya penggunaan materi yang relevan secara kultural dalam meningkatkan kemampuan menyimak siswa